Nora Kelly : Badlands - Book 5 - Preston, Douglas J.; Child, Lincoln (New York : GCP, 2025)
"In the New Mexico badlands, the skeleton of a woman is found-and the case is assigned to FBI Agent Corrie Swanson. The victim walked into the desert, shedding clothes as she went, and died in agony of heatstroke and thirst. Two rare artifacts are found clutched in her bony hands-lightning stones used by the ancient Chaco people to summon the gods. Is it suicide or... sacrifice? Agent Swanson brings in archaeologist Nora Kelly to investigate. When a second body is found-exactly like the other-the two realize the case runs deeper than they imagined. As Corrie and Nora pursue their investigation into remote canyons, haunted ruins, and long-lost rituals, they find themselves confronting a dark power that, disturbed from its long slumber, threatens to exact an unspeakable price"--
Keywords: Detective and mystery fiction; Novels